2016
DOI: 10.1007/s10047-016-0920-y
|View full text |Cite
|
Sign up to set email alerts
|

Changing pulsatility by delaying the rotational speed phasing of a rotary left ventricular assist device

Abstract: Continuous-flow left ventricular assist devices (LVADs) have improved the prognosis of end-stage heart failure. However, continuous-flow LVADs diminish pulsatility, which possibly result in bleeding, aortic insufficiency, and other adverse effects. We previously developed a novel control system for a continuous-flow LVAD (EVAHEART; Sun Medical), and demonstrated that we could create sufficient pulsatility by increasing its rotational speed (RS) in the systolic phase (Pulsatile Mode) in the normal heart model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Travis et al 22 reported that PF LVAD patients at a low support level restored SHE values within 2.5% of baseline normal values, whereas CF LVAD patients at low support had diminished SHE values by more than 93% of baseline normal values, and this effect was even more pronounced at a higher support level. 22 Date et al 6 investigated pulsatility using EEP under CF LVAD support with pump speed modulation, and the SHE value increased by 244% from the CF mode in an animal experiment. 6 When the trans-valve LVAD does not apply hydrodynamic pulsatile energy into blood flow, the SHE value is lower than that of PF LVAD and CF LVAD with the speed modulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Travis et al 22 reported that PF LVAD patients at a low support level restored SHE values within 2.5% of baseline normal values, whereas CF LVAD patients at low support had diminished SHE values by more than 93% of baseline normal values, and this effect was even more pronounced at a higher support level. 22 Date et al 6 investigated pulsatility using EEP under CF LVAD support with pump speed modulation, and the SHE value increased by 244% from the CF mode in an animal experiment. 6 When the trans-valve LVAD does not apply hydrodynamic pulsatile energy into blood flow, the SHE value is lower than that of PF LVAD and CF LVAD with the speed modulation.…”
Section: Discussionmentioning
confidence: 99%
“…22 Date et al 6 investigated pulsatility using EEP under CF LVAD support with pump speed modulation, and the SHE value increased by 244% from the CF mode in an animal experiment. 6 When the trans-valve LVAD does not apply hydrodynamic pulsatile energy into blood flow, the SHE value is lower than that of PF LVAD and CF LVAD with the speed modulation. However, the trans-valve LVAD has an advantage in that it can preserve pulsatility without any complicated mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new concept of the axial VAD in 1989 has several merits. An axial VAD serially connected with the natural heart, such as the valvo pump, can support blood circulation with pulsatile flow generated by the natural heart without pump speed modulation . However, realization of the valvo pump concept has not occurred because it is difficult to develop a miniature high‐power motor to meet the requirement of the valvo pump under current motor technology.…”
Section: Discussionmentioning
confidence: 99%
“…An axial VAD serially connected with the natural heart, such as the valvo pump, can support blood circulation with pulsatile flow generated by the natural heart without pump speed modulation. 15,16 However, realization of the valvo pump concept has not occurred because it is difficult to develop a miniature high-power motor to meet the requirement of the valvo pump under current motor technology. Thus, a new concept of the valvo pump was proposed: The trans-valve axial VAD, in which the motor is installed in the left ventricle, and the impeller is placed at the aortic valve position.…”
Section: Discussionmentioning
confidence: 99%